7(4-3x)-(8,5-x)= 4-3(x -8)3(0.5m+0.7n)-5(0.3m-0.4n)

7(4-3x)-(8,5-x)= 4-3(x -8) & 3(0.5m+0.7n)-5(0.3m-0.4n)
Гость
Ответ(ы) на вопрос:
Гость
28-21х-8,5+х=4-3х+24 19,5-20х=-3х+28 -20х+3х=28-19,5 -17х=8,5 х=8,5:(-17) х=-0,5 проверка; 7(4-3(-0,5)-(8,5-(-0,5)=4-3(-0,5-8) 38,5-9=4+25,5 29,5=29,5 Ответ:х=-0,5. ну,а тут надо просто сократить 3(0,5m+0,7n)-5(0.3m-0,4n)=1,5m+2,1n-1,5m+2n=4,1n Ответ:4,1n.
Гость
28-21х-8,5+х=4-3х+24 19,5-20х=-3х+28 -20х+3х=28-19,5 -17х=8,5 х=8,5:(-17) х=-0,5 другой не понимаю.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы